Laryngeal Mucosa Alterations in Mice Model of Gastroesophageal Reflux: Effects of Topical Protection. (11th March 2020) - Figueiredo, Aline A.; Sales, Thiago M. A. L.; Nicolau, Lucas A. D.; Nunes, André A. A.; Costa‐Filho, Humberto B.; Moreira, Rhubens L. R.; Nascimento, Renata R.; Sousa, Maria K. A.; Silva, Lorena D.; Carmo‐Neto, João P.; Sidou, Flávio M. N. O.; Paula, Suliana M.; et al.
Abstract : Objectives/Hypothesis: The objectives of this study were to evaluate laryngeal inflammation and mucosal integrity in a murine model of reflux disease and to assess the protective effects of topical agents including alginate, hyaluronic acid, and cashew gum. Study Design: Animal study. Methods: A surgical murine model of reflux disease was evaluated at 3 or 7 days postsurgery, and laryngeal samples were collected to measure inflammation (wet weight and myeloperoxidase [MPO]) and mucosal integrity (transepithelial resistance [TER] and mucosal permeability to fluorescein). Additional groups of animals were administered one of several topical agents (alginate, hyaluronic acid, or cashew gum) daily, and laryngeal inflammation and mucosal integrity were evaluated at 3 days postsurgery. Results: At 3 days, and not 7 days postsurgery, we observed increased laryngeal wet weight and MPO, decreased laryngeal TER, and increased laryngeal mucosa permeability. Alginate partially decreased laryngeal inflammation (wet weight and not MPO) and dramatically improved laryngeal mucosal integrity. Conversely, hyaluronic acid eliminated the inflammation; however, it had no effect on laryngeal mucosal integrity impairment. Cashew gum eliminated laryngeal inflammation as well as the impairment in laryngeal mucosal integrity. Conclusions: This study shows that a surgical model of reflux disease induced laryngeal inflammation and impairment in laryngeal barrier function. These observed alterations were partially attenuated by alginate and hyaluronic acid and completely reversed by cashew gum. Level of Evidence: NA Laryngoscope, 2020